2014
DOI: 10.1590/0103-6440201300027
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Toothpastes Containing Natural Extracts, Chlorhexidine or Triclosan

Abstract: The objective of this in vitro study was to evaluate the antimicrobial effect of toothpastes containing natural extracts, chlorhexidine or triclosan. The effectiveness of toothpastes containing natural extracts (Parodontax®), 0.12% chlorhexidine (Cariax®), 0.3% triclosan (Sanogil®) or fluoride (Sorriso®, control) was evaluated against yeasts, Gram-positive and Gram-negative bacteria using the disk diffusion method. Water was used as a control. Disks impregnated with the toothpastes were placed in Petri dishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
2
12
1
1
Order By: Relevance
“…low abrasive potential of the dentifrice, resulting in poor mechanical removal of biofilm; or a low in vivo concentration, which may have not been enough to produce the same effects observed in vitro, due to salivary clearance, substantivity and other factors inherent to the human body. In contrast, the control dentifrice was efficient in reducing biofilm accumulation, which corroborates previous studies that evaluated the potential of triclosan-based dentifrices (17,(22)(23)(24). The ripe fruit of E. uniflora contains flavonoids, which are chemical markers of anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…low abrasive potential of the dentifrice, resulting in poor mechanical removal of biofilm; or a low in vivo concentration, which may have not been enough to produce the same effects observed in vitro, due to salivary clearance, substantivity and other factors inherent to the human body. In contrast, the control dentifrice was efficient in reducing biofilm accumulation, which corroborates previous studies that evaluated the potential of triclosan-based dentifrices (17,(22)(23)(24). The ripe fruit of E. uniflora contains flavonoids, which are chemical markers of anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 89%
“…These data support the findings of this study, in which the experimental dentifrice exhibited in vitro antibacterial activity against streptococci and lactobacilli. As expected, the conducted study also confirmed the antimicrobial potential of the control dentifrice containing triclosan, which is a chemical agent recognized in literature as having antimicrobial properties (17).…”
Section: Discussionsupporting
confidence: 85%
“…The results of the present study is in contrast with that of De Rossi A et al (2014) 37 who conducted an in vitro study to evaluate the antimicrobial effect of toothpastes containing natural extracts, 0.12% chlorhexidine, 0.3% triclosan and conventional toothpaste (control) and found that all formulations, except for conventional toothpaste showed antimicrobial activity against Gram-positive bacteria and yeasts (p>0.05) whereas the toothpaste containing natural extracts was the only product that was able to inhibit the growth of Gram-negative bacteria (Pseudomonas aeruginosa). The difference might be explained by the different herbal components which demonstrated antiseptic,anti-inflammatory and antimicrobial propertiesas well as the synergistic interaction of the principal components of the herbs contributing to their antimicrobial property.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, HOCl showed a significant effect on Gram positive bacteria but did not exceed the effect of chlorhexidine. Chlorhexidine has shown better effect on Gram positive microorganisms but less on Gram negative microorganisms (17,18). The antimicrobial action of HOCl appears to be greater in Gram negative than in Gram positive possibly because Gram negative bacteria has sulfur and hem groups (rich in iron) in its membrane which causes an irreversible reaction HOCl/membrane proteins, producing structural damage, and altering cell permeability, affecting bacterial viability in Gram negative bacteria (19,20).…”
Section: Discussionmentioning
confidence: 99%